Benefits of simulation-based education in hospital emergency departments: A systematic review - Shandiz Moslehi; Gholamreza Masoumi; Fahimeh Barghi-Shirazi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The emergency department is one of the most important parts of all hospitals. For this reason, many simulation programs are performed in this department to increase the knowledge, skills, and productivity of health-care workers. The purpose of this study was to identify the benefits of simulation in hospital emergency departments. MATERIALS AND METHODS: In the present systematic study, using "AND" and "OR" operators, we searched for the keywords "benefits," "simulation," and "hospital emergency department" in PubMed, Web of Science, Scopus, Google Scholar as well as Persian language databases such SID, Magiran, Irandoc, and Iran Medex. Then, a three-step screening process was used to select studies relevant to simulation and hospital emergency from 2005 to 2021 using the PRISMA checklist, and finally, the obtained data were analyzed. RESULTS: A total of three main groups, each with several subgroups, were extracted and identified as the benefits of using simulation in hospital emergency departments. They included improving the diagnosis of the disease (rapid prediction of the disease, rapid diagnosis, and patient triage), improving the treatment process (improvement of treatment results, anticipation of admission and discharge of patients, acceleration of interventions, and reduction of medical errors), and improving knowledge and skills (improvement of the speed of decision-making, staff's acquisition of knowledge and skills, simple, convenient, and low-cost training, improvement of staff's preparedness in crisis). CONCLUSION: Based on the results of the present study, it is suggested to develop some training programs in order to help staff upgrade their knowledge and performance as well as acquire practical skills and also to improve the diagnosis and treatment process in hospital emergency departments. Virtual methods are also proposed to be applied as potential and cost-effective platforms for learning, teaching, and evaluating the staff of hospital emergency departments.